Cyriax manipulation versus Mulligan’s mobilization in subacromial pain syndrome - Fatima, Noor; Ambreen Zahid (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
The study aimed to compare the effectiveness of chiropractic manipulation and Mulligan’s mobilization in reducing pain, improving range of motion, and enhancing functional outcomes in individuals with subacromial pain syndrome. This was a randomized controlled trial (RCT) at DHQ Jhelum, CMH Jhelum, and Jhelum Sports Complex, Pakistan. A total of 62 participants with subacromial pain syndrome were randomly assigned to a chiropractic manipulation group (n = 31) or a Mulligan’s mobilization with movement (MWM) group (n = 31). Both groups received their respective interventions over a set treatment period. Pain intensity (VAS), functional disability (SPADI), and shoulder range of motion (flexion, extension, abduction, internal and external rotation) were measured pre- and post-intervention. The mean age was 46.71 ± 8.30 years in the chiropractic group and 47.03 ± 7.74 years in the MWM group. Baseline VAS scores were 7.58 ± 1.12 and 7.32 ± 1.14, decreasing post-intervention to 2.45 ± 1.34 and 4.32 ± 1.33, respectively. SPADI scores improved from 63.93 ± 6.24 to 32.97 ± 6.67 in the chiropractic group and from 62.74 ± 5.62 to 42.58 ± 5.46 in the MWM group. Flexion, extension, abduction, internal rotation, and external rotation ROM all increased in both groups, with chiropractic improving from 117.42°, 38.70°, 94.21°, 37.65°, and 52.11° to 155.32°, 47.64°, 126.68°, 50.75°, and 69.13°, and MWM from 118.10°, 38.36°, 95.82°, 37.23°, and 52.74° to 145.56°, 44.91°, 118.34°, 46.12°, and 65.70°, respectively. Both chiropractic manipulation and Mulligan’s mobilization with movement effectively reduced pain, improved range of motion, and enhanced function in individuals with subacromial pain syndrome. Chiropractic manipulation consistently produced superior outcomes across all parameters, likely due to combined biomechanical and neuro-physiological effects.